Leishmaniasis of the lip diagnosed by lymph node aspiration and treated with a combination of oral ketaconazole and intralesional sodium stibogluconate - Biju Vasudevan; Ashish Bahal (Wolters Kluwer Medknow Publications, 2011)
A 26-year-old male who presented to the dermatology OPD with complaints of a swelling on his lip of 6 months' duration was on examination found to have a solitary ulcerated nodule over the lip and an enlarged submental lymph node. Skin smear and biopsy from the lesion did not yield the diagnosis. Needle aspiration from the draining lymph node revealed the diagnostic Leishman-Donovan bodies. The patient responded to treatment with a combination of oral ketoconazole and intralesional sodium stibogluconate. We report this case because of both the unusual location of the lesion and the unusual method of diagnosis and treatment.